2008
DOI: 10.2320/matertrans.mra2007135
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Predict the Thermal Conductivity of Composites with Coated Spherical Fillers and Imperfect Interface

Abstract: An examination of the concept of a microgeometry proposed by Benveniste reveals that the thermal conductivity of the concentric sphere adopted by generalized self-consistent model (GSCM) is equal to that of the composite. It is also noted that the thermal conductivities of the composite with spherical fillers predicted by GSCM and modified Eshelby model (MEM) are the same. These equivalencies enable to propose a simple and alternative approach for determining the thermal conductivity of the composite with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Landauer developed a model to predict effective thermal conductivity of porous media which is defined as a mixture of two phases [4][5][6][7]. The percolation model assumes a completely random distribution of solid and gas that is equivalent to an Effective Medium Theory (EMT) [8][9][10]. Kou et al [3] proposed a self-similar fractal model.…”
Section: List Of Symbolsmentioning
confidence: 98%
“…Landauer developed a model to predict effective thermal conductivity of porous media which is defined as a mixture of two phases [4][5][6][7]. The percolation model assumes a completely random distribution of solid and gas that is equivalent to an Effective Medium Theory (EMT) [8][9][10]. Kou et al [3] proposed a self-similar fractal model.…”
Section: List Of Symbolsmentioning
confidence: 98%
“…In this regard, there are some pioneering works that have followed mainly two modelling approaches. One approach is to consider the interface as a third phase material and to then derive exact solutions based on a mean-field scheme [5,6]. This approach uses plausible yet no rigorous assumptions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…where q is the fraction of phonons within a critical angle of incidence, p is the transmission probability of phonons within the critical angle of incidence fraction, and Z (Z=ρv) is the acoustic impedance. The subscripts ''in'' and ''tran'' in Equations (5)(6) refer to the incident and transmitted sides of the phonons, respectively. v´ is defined as follows:…”
Section: New Generalized Modelling Approachmentioning
confidence: 99%
“…The high-temperature gradient results in high thermal stresses, which may cause de-bonding of the interface, thus reducing the function and reliability of the systems. A better understanding of temperature and thermal flux distributions in the bonded media is critical in many applications.In the literature, numerous studies have been reported on the investigation of thermal conduction in particle composites and multi-layered media [1][2][3][4][5][6][7][8][9][10]. To the authors' best knowledge, the thermal behavior of bi-layer materials with an interface inclusion has not been investigated for finite media.…”
mentioning
confidence: 95%